PENGARUH METODE CERITA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS III DI MI SIROJUL FALAH - Yani Sugiarti; Oking Setia Priatna; Kholil Nawawi (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2018)
This study aims to determine the process of applying the method of class 3 stories on the subjects of SKI in MI SIrojul Falah, and to know the effect of 3rd class story method on the subjects of SKI in MI SIrojul Falah. The approach used in this study is quantitative research with the type of quasi-experimental research, in this study the selection of samples on experimental quasi type Non Equivalent Control Group Design is not done random sample selection but deliberately selected by the researchers ie with each sample control class 31 students and experimental class of 34 students. The instruments used in this research are: test, observation, and documentation. The process of applying story method on SKI subjects through ten stages are: Place of story, sitting position, story language, interesting, teacher intonation, appearance of figures, emotional appearance, sound imitation, moving, mastery of students who are not serious. The average post-test of the control class is 75.81 and the average post-test of the experimental class is 77.06 so Based on the acquisition of that value that -t arithmetic> -t table (-14.219> -2.035), for the experimental class then Ha be accepted. This means that in this experimental class the value of the test using the story method is higher than by using learning that does not use the method of story (lecture). In addition, researchers also observed the activities of teachers in the application of story methods, observation data resulted in the percentage of control class teachers without using the story method by 45%, and the percentage of experimental class teachers by applying the story method by 87%. So it can be concluded that there is a significant influence by applying the story method in learning, if the teacher knows and can apply the stages in the story method properly and correctly. So the application of story methods can affect student learning outcomes on SKI subjects are said to be effective and there are significant changes or improvements. This story method can be one of the alternative learning methods that can be applied in the learning process.